Eco-friendly synthesis of low-cost antibacterial agent (brown attapulgite-Ag nanocomposite) for environmental application - Abdulkareem, Mustafa A.; Joudi, Mayada S.; Ali, Aisha H. (Chemical Data Collections, 2022)
This work includes the eco-friendly synthesis of brown attapulgite-Ag nanocomposite by the in situ bio reduction of Ag ions using leaf extract of ziziphus spina christi L. The resulted nanocomposite was characterized using XRD, SEM, EDX-mapping and TEM. The results prove the presence of silver nanoparticles with a diameter of 27–44 nm and attapulgite rods within the nanocomposite. The brown attapulgite-Ag nanocomposite was used as a colorizing antibacterial agent for pentalite emulsion paint (pep). Four different weights of nanocomposite (0.1, 0.5, 1.5 and 3 g) was added to 10 ml of pep and suspended in 10 ml of water. The antibacterial results show that this paint is useful to inhibit the bacteria growth in the presence of brown attapulgite-Ag nanocomposite. The thermal stability of brown attapulgite-Ag nanocomposite was studied at 100 °C and the XRD measurement proves that there is no change occurred for brown attapulgite-Ag nanocomposite after thermal treatment. Furthermore, the acid and base stability of brown attapulgite-Ag nanocomposite were examined and the results of ICP-OES prove the stability of the prepared nano colorizing additive. [Display omitted] .